Effect of Mindfulness on the Stress–Recovery Balance in Professional Soccer Players during the Competitive Season - Holguín Gastélum, Joaquín; Ramos Jimenez, Arnulfo; QUEZADA, TRINIDAD; Cervantes-Borunda, Monica Sofia; Hernández-Torres, Rosa Patricia (2020)
Professional athletes are subjected to constant stress that often leads them to exceed their capacities and lose their homeostasis, which without a proper recovery program can lead to injury, chronic fatigue, and overtraining. This work examines the effect of six weeks of a psychological intervention called Mindful Sports Performance Enhancement (MSPE), on the stress–recovery balance in professional soccer players during a competitive season. Methods: The RESTQ-76 Sport psychometric questionnaire and heart rate variability (HRV) were used as psychometric and physiological evaluation methods. Under a longitudinal case–control study and having complied with bioethical procedures, 42 professional soccer players (22 control without treatment and 20 experimental), age 17 ± 1 year, weight 63 ± 11 kg, and height 172 ± 7 cm, were analyzed. Results: RESTQ-76 Sport increased the stress–recovery balance and global recovery (p < 0.5), but decreased global stress. The stress–recovery balance values measured by the nonlinear indicators of the HRV: SD1, SD2, SS, and S:PS, were not modified. Conclusions: Six weeks of MSPE improves the stress–recovery balance in third-division professional soccer players during the competitive season, reduces stress, and increases recovery. These positive effects were not observed in the nonlinear indicators of the HRV: SD1, SD2, SS, and S:PS.